Karl Marx’s Criticism on Religion - Juhansar Andi Latief (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2011)
This article discusses about the uniqueness of religion among other academic disciplines. Religion is almost exclusively approached as an object of study. This paper presents a descriptive criticism of Islam in Marx's critique of religion. The study then found that Islam and Marxism is essentially a contradiction particularly striking in view of the unity-an. Marx, based on the philosophy of Marxism; man- made ​​religion and religion does not make the man. However, Muslims believe in the spiritual concept of the infinite in which Islam describes the man as the ground; land; ground, or it can be said that religion, in this case, God created man, not vice versa.